2021
DOI: 10.3390/educsci11030121
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Digital Device Usage on Student Academic Performance: A Case Study

Abstract: The aim of this investigation was to explore student behaviour when students brought their own digital devices into a lecture theatre. A total of 361 undergraduate psychology students from the University of Liverpool who used at least one digital device during lecture time fully completed an online questionnaire (159 first-, 124 second- and 78 third-year psychology students) during the 2018–2019 academic year. Although all the three years of undergraduate students brought laptops and/or smartphones into a lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The finding that access to PowerPoint during the revision week increased for first-class students, and remained the same for those in the middle grades (2:1 and 2:2) while dropping further for failing and third-class students suggest that those working at different grade levels will respond differently to any challenges of access. Indeed, a recent study looking at Veterinary Science and Psychology student's behaviour during the recent pandemic (Limniou et al, 2021) showed a similar relationship between student use of digital tools during the lockdown and their self-regulation which in turn demonstrated an effect on grade boundaries. In considering the use of recorded lectures through Stream Capture, an unexpected finding was that this technology was used more by students in non-strike years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The finding that access to PowerPoint during the revision week increased for first-class students, and remained the same for those in the middle grades (2:1 and 2:2) while dropping further for failing and third-class students suggest that those working at different grade levels will respond differently to any challenges of access. Indeed, a recent study looking at Veterinary Science and Psychology student's behaviour during the recent pandemic (Limniou et al, 2021) showed a similar relationship between student use of digital tools during the lockdown and their self-regulation which in turn demonstrated an effect on grade boundaries. In considering the use of recorded lectures through Stream Capture, an unexpected finding was that this technology was used more by students in non-strike years.…”
Section: Discussionmentioning
confidence: 94%
“…A VLE can be used in a variety of ways from a simple repository of materials up to a fully developed blended learning environment, however either case the VLE will tend to be one of the central focus points of a course, with students accessing materials and learning through the VLE and university course systems rather than on external sites and tools , or social media (Limniou, 2021). As such VLE data traces can be an important way of researching student behaviour within the digital environment.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the recent COVID-19 disruption may have accelerated the exploration of a more expansive learning ecology that encourages higher level self-directed learning across formal and informal learning environments. For example, in flipped classrooms, students can watch lecture videos or access learning resources provided in the formal learning environment, while well-designed formal learning environments will, at the same time, allow students to explore and draw on their sources for learning in informal learning environments [92].…”
Section: Self-directed Learning In the Digital Learning Ecologymentioning
confidence: 99%
“…Taking a close look at a higher institution classroom nowadays, a proliferation of mobile devices can be seen. This can be accounted for partly by the improvement in the infrastructure of most Higher Institutions which allow students to bring their own devices (BYOD) into the classroom [24]. This has resulted in a shift to mobile learning [23].…”
Section: Introductionmentioning
confidence: 99%